2020
DOI: 10.3390/rs12030391
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing and Social Sensing Data Reveal Scale-Dependent and System-Specific Strengths of Urban Heat Island Determinants

Abstract: Urban natural surfaces and non-surface human activities are key factors determining the urban heat island (UHI), but their relative importance remains highly controversial and may vary at different spatial scales and focal urban systems. However, systematic studies on the scale-dependency system-specificity remain largely lacking. Here, we selected 32 major Chinese cities as cases and used Landsat 8 images to retrieve land surface temperature (LST) and quantify natural surface variables using point of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 49 publications
(97 reference statements)
1
17
0
5
Order By: Relevance
“…This finding indicates that the scale and extent have a certain effect on the factors that influence the RHI. This result is similar to that of Luan et al 43 . Therefore, it is necessary to control the expansion of construction land as much as possible, original sand and gravel surfaces should not be covered and the area of the impervious surface should be controlled.…”
Section: Discussionsupporting
confidence: 93%
“…This finding indicates that the scale and extent have a certain effect on the factors that influence the RHI. This result is similar to that of Luan et al 43 . Therefore, it is necessary to control the expansion of construction land as much as possible, original sand and gravel surfaces should not be covered and the area of the impervious surface should be controlled.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found that the LST retrieved by the radiative transfer equation algorithm can obtain the highest accuracy in the high atmospheric water vapor environments [7,10,53]. Therefore, this study chose the radiative transfer equation algorithm proposed by Jiménez-Muñoz et al [54] to calculate LST.…”
Section: Lst and Relative Lst Calculationmentioning
confidence: 99%
“…In the next step, it is necessary to identify the heat corridor through constructing the resistance surface [60], methods like circuit theory and the leastcost method can be employed. Second, the MSPA model is sensitive to the scale effect (i.e., the resolution of the raster image) [41], as well as the UHI determinants [10]. Hence, scale effects (grain size and spatial extent) must be considered in future related research.…”
Section: Limitations and Further Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, paved surfaces, building walls, roofs and other impervious surfaces efficiently absorb solar radiation and have a greater heat capacity and thermal conductivity in comparison to natural surfaces (grass, trees, etc.) (Akbari & Kolokotsa, 2016;Luan et al, 2020). Urban surfaces re-emit this heat, acting as heat-sources, while forests and water act as heat-sinks (Yu et al, 2020).…”
Section: Urban Heat Processesmentioning
confidence: 99%